DA PENA À PELÍCULA: AS PERSONAGENS DE CARANDIRU - Souza, Melody Pablos (2009)
This study focuses the adaptation of the book Estação Carandiru, written by Drauzio Varella, to the movies, concerning the construction of the characters. Therefore, a listing of the characters and their characteristics was made, from both the book and the movie. The main objective is to understand the choices made in this dialog between medias, from where the movie Carandiru, by Hector Babenco, originated, considering that there was a great reduction in the number of characters. For this analysis, the methodological process adopted was the descriptive research. It was verified that most part of the characters origins come from the fusion of literary characters. But it was also found that literary characters were dismembered and some of them were eliminated. No new character was found.(AU)